On the Well-posedness of the Magnetic, Semi-relativistic Schrödinger-Poisson System - Vougalter, Vitali (Discontinuity, Nonlinearity, and Complexity, 2026)
We prove global existence and uniqueness of strong solutions for the Schrödinger-Poisson system in the repulsive Coulomb case with relativistic, magnetic kinetic energy.